The Effectiveness of Oil Essensiil Foot Massage Citronella of Lavender and Blood Pressure Hypertension Elderly Patients - Zaenal Amirudin; Suryo Pratikwo; Rr. Sri Sedjati (Jurnal Riset Kesehatan, 2014)
This study aims to determine the difference in effectiveness between the foot massage with lavender essential oils of citronella oil to decrease blood pressure in elderly hypertensive patients in Pekalongan City. This type of research is randomized pre-post test design with control". A total of 21 respondents were recruited by purposive sampling technique. Massage is done on foot for 20 minutes each day for 3 days, using lavender oil essensiil, and citronella oil. Data were obtained by measuring the blood pressure before and after massage and analysis using descriptive statistical tests. Bivariate analysis to determine the mean difference between the 2 treatment pre and post treatment using paired Student's t-test, the difference between the 2 groups using Independent t-test test. one-way ANOVA. The results showed that the foot massage using lavender essensiil oil and citronella on effective control for lowering the blood pressure of elderly hypertensive patients . However, lavender oil essensiil were more likely to experience a decrease in blood pressure compared with citronella oil and control.